Animal models of Shiga toxin-producing Escherichia coli infection - Kyung-Hyo Do; Kwangwon Seo (Journal of Applied Animal Research)
Shiga toxin-producing Escherichia coli (STEC) is widely distributed in the environment and is recognized for its association with severe illnesses in both animals and humans. As effective treatments and preventive measures remain limited, it becomes crucial to understand the mechanisms underlying STEC-induced diseases. Animal models allow analyzing the pathophysiology of diseases. However, current models do not accurately reproduce the full spectrum of diseases caused by STEC. In this study, we discussed the key characteristics and constraints of five animal models (mouse, rabbit, chicken, dog, and pig) used to study STEC infections.